2011
DOI: 10.1128/iai.05191-11
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Phenotypic Characteristics of Alternative Activation Induced in Human Monocytes by Interleukin-4 or the Parasitic Nematode Brugia malayi

Abstract: Human monocytes from patients with patent filarial infections are studded with filarial antigen and express markers associated with alternative activation of macrophages (M⌽). To explore the role of filaria-derived parasite antigen in differentiation of human monocytes, cells were exposed to microfilariae (mf) of Brugia malayi, and their phenotypic and functional characteristics were compared with those of monocytes exposed to factors known to generate either alternatively (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 52 publications
9
53
0
Order By: Relevance
“…In fact, human monocytes can be activated using either LPS/IFN-␥ or IL-4/IL-13 to promote development of M1-or M2-type cells, respectively (16,(24)(25)(26). While M1 macrophages produce an array of inflammatory cytokines, including IL-1␣, IL-1␤, TNF-␣, and IL-6, M2 macrophages in humans can be distinguished by their production of a set of chemokines, including CCL13, CCL18, and CCL22 (12,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, human monocytes can be activated using either LPS/IFN-␥ or IL-4/IL-13 to promote development of M1-or M2-type cells, respectively (16,(24)(25)(26). While M1 macrophages produce an array of inflammatory cytokines, including IL-1␣, IL-1␤, TNF-␣, and IL-6, M2 macrophages in humans can be distinguished by their production of a set of chemokines, including CCL13, CCL18, and CCL22 (12,26).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue macrophages can also be subdivided into at least three populations: M1, characterized by an inflammatory profile induced primarily during a Th1 response; M2, which have both anti-inflammatory and tissue repair functions (9), largely driven by IL-4 and/or IL-13; and finally, regulatory macrophages (Mreg) that are considered to be the primary source of innate . Although there is increasing evidence indicating human monocytes can be polarized in vitro with LPS and gamma interferon (IFN-␥) into M1, with IL-4/IL-13 into M2, or with a combination of immune complexes and Toll-like receptor (TLR) ligands into Mreg (15,16), little is known about the ontogeny of these subsets.…”
mentioning
confidence: 99%
“…Furthermore, we have done extensive in vitro studies showing that M f s need not be differentiated prior to polarization with IL-4. In fact, short-term exposure of M f s to IL-4 is suf fi cient to induce the AAM F phenotype in human cells [ 42 ] . In addition, the mf stage of B. malayi or soluble factors from mf induce a programmed response very similar to that induced by IL-4, resulting in upregulation of MRC1 or CD206, CCL15, CCL17, CCL18, CCL22, CD273, and CD274.…”
Section: Humansmentioning
confidence: 99%
“…Previous studies 8 have shown that CLEC10a mRNA expression is increased on M2 MDM and there have been reports of increases on macrophages in a number of diseases [43][44][45] . However, to our knowledge there have been no studies of both mRNA and protein expression.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 99%